Legal Analysis on Remixing Songs Using Artificial Intelligence (Ai) Technology - Abdad, Saffa Abdullah; Safira Hafis Pradina; Alisa Zahra Sakdiya; Anissa Nur Zahrani (Law and Justice, 2024)
The rapid advancement of technology has profoundly influenced the music industry, with Artificial Intelligence (AI) emerging as a key tool, especially in song remixing. AI, which has been evolving since the 20th century, now plays a significant role in creative processes, leading to legal concerns regarding copyright, ownership, and the rights of original creators. In Indonesia, creative works, including music, are protected under Law Number 28 of 2014 on Copyright. This study investigates the legal implications of using AI technology for song remixing within the framework of Indonesian law. Employing a normative legal research method, the study examines statutory regulations, case studies, and legal precedents to assess the legal status of AI-generated remixes. The research aims to determine whether remixing songs with AI is permissible under Indonesian law and to identify the conditions under which such practices may violate copyright protections. The results indicate that AI-generated song remixes are legally permissible, provided they comply with existing copyright laws. The study identifies key challenges, particularly in defining the originality of AI-generated works and determining authorship. The findings underscore the necessity for clear legal guidelines to address the growing influence of AI in the creative industry. In conclusion, while AI offers innovative opportunities in music production, it also necessitates careful legal consideration to protect the rights of original creators. This study contributes to the ongoing discussion on AI and intellectual property, highlighting the need for legal frameworks that balance technological progress with the protection of creators' rights.     Setiap aspek dalam kehidupan sehari-hari sudah mulai berubah pada tahap ketergantungan terhadap teknologi. Salah satu yang popular dengan munculnya kecerdasan buatan atau dikenal dengan artificial intellengence disingkat dengan AI. Perkembangan AI dimulai sejak abad ke-20 hingga sekarang yang dapat dimanfaatkan manusia dalam pembuatan remix lagu. Negara Indonesia merupakan negara hukum, maka pengaturan penciptaan lagu pada Undang-Undang Nomor 28 Tahun 2014. Penulisan artikel ini menggunakan metode penelitian normatif dengan mengkaji undang-undang dan melihat kondisi praktik di masyarakat dengan perspektif undang-undang. Penulisan ini guna menambah wawasan dan pengetahuan terkait dengan remix lagu yang marak dilakukan dengan menggunakan kecerdasan buatan atau AI. Remix lagu dengan menggunakan teknologi AI menjadi suatu hal yang sah untuk dilakukan selama hal ini sesuai dengan setiap ketentuan yang sudah diatur dalam peraturan perundang-undangan.